Long-term in vivo dissolution of thermo- and pH-responsive, 19 F magnetic resonance-traceable and injectable polymer implants - Jirát-Ziółkowska, Natalia; Vít, Martin; Groborz, Ondřej; Kolouchová, Kristýna; Červený, David; Sedláček, Ondřej; Jirák, Daniel (Nanoscale advances, 2024)
19 F magnetic resonance ( 19 F MR) tracers stand out for their wide range of applications in experimental and clinical medicine, as they can be precisely located in living tissues with negligible fluorine background. This contribution demonstrates the long-term dissolution of multiresponsive fluorinated implants designed for prolonged release. Implants were detected for 14 (intramuscular injection) and 20 (subcutaneous injection) months by 19 F MR at 4.7 T, showing favorable MR relaxation times, biochemical stability, biological compatibility and slow, long-term dissolution. Thus, polymeric implants may become a platform for long-term local theranostics.